Non-Newtonian mixed thermo-elastohydrodynamics of hypoid gear pairs. (September 2018) - Mohammadpour, M; Theodossiades, S; Rahnejat, H; Dowson, D
Transmission efficiency is the main objective in the development of vehicular differential systems, comprising hypoid gear pairs. The overall aim is to contribute to improved vehicle fuel efficiency and thus levels of harmful emissions for modern desired eco-drive axles. Detailed predictive analysis plays an important role in this quest, particularly under realistic operating conditions, comprising high contact loads and shear rates. Under these conditions, the hypoid gear pairs are subject to mixed non-Newtonian thermo-elastohydrodynamic conditions, which is the approach undertaken in this paper. Such an approach for hypoid gear pair has not hitherto been reported in the literature.